STRENGTHENING THE PANCASILA STUDENT PROFILE IN STUDENT CHARACTER DEVELOPMENT AT MTS NUR HADI MUARA JAWA - Nurlinita (English Study Program University of Pasir Pengaraian, 2025)
The Pancasila Student Profile serves as a fundamental framework in Indonesian education aimed at developing students’ character, competence, and national identity in response to global challenges. This study examines the implementation of the Pancasila Student Profile in strengthening student character development at MTs Nur Hadi Muara Jawa, an Islamic junior secondary school. Using a qualitative descriptive research design, data were collected through observations, in-depth interviews with school leaders and teachers, and document analysis of curriculum plans, school programs, and institutional policies. The findings indicate that the integration of the Pancasila Student Profile into curricular, co-curricular, and extracurricular activities has positively influenced students’ religious values, independence, cooperation, critical thinking, creativity, and global awareness. The madrasah context, which integrates Islamic values with national ideology, provides a supportive environment for internalizing Pancasila principles. However, challenges remain, particularly related to teacher readiness, program consistency, and evaluation mechanisms. The study concludes that strengthening the Pancasila Student Profile in madrasah education is effective in fostering holistic student character, provided that continuous teacher professional development and institutional support are maintained.